Situational Leadership: A Supporter in Educational Planning at the Akpol Institute of Education And Training - Wulandari, Istri; Raharjo, Tri Joko; Widada, Tri; Arbarini, Mintarsih (Journal of Ecohumanism, 2025)
Leadership in educational institutions is a key factor in shaping the quality of education, the development of institution culture, and the overall success of students and staff. Police academies represent a unique segment of the educational landscape, where cadets must acquire not only theoretical knowledge but also practical skills essential for law enforcement. The study aimed to investigate situational leadership at the Police Academy that is able to provide implications for educators, students and higher education institutions. Data sources are derived from primary data. Primary data was taken from the answers of respondents through questionnaires that were distributed directly. The population is teaching staff at the police academy education and training institution. This finding that the leadership of the governor of Akpol and his staff is able to support the planning of educators so that educators understand the goals they want to achieve in learning, meet the needs of educators according to their qualifications and competencies in order to improve the quality of educational institutions.